Echocardiographic assessment of left ventricular systolic function in neonatal calves with naturally occurring sepsis or septic shock due to diarrhea. (October 2019) - Naseri, Amir; Sen, Ismail; Turgut, Kursad; Guzelbektes, Hasan; Constable, Peter D.
Abstract: Sepsis is associated with clinically relevant cardiovascular changes. The objectives of this study were to evaluate the clinical value of echocardiography for monitoring left ventricular (LV) systolic function in septic calves. A prospective longitudinal study was performed using a convenience sample. Twenty septic calves and 10 healthy calves were enrolled in the study. Arterial blood pressure (BP) was measured and M-mode echocardiography performed to characterize LV systolic function; the latter included measurement of ejection fraction, EF; stroke volume, SVI and cardiac output indexed to body weight, CI; E-point of septal separation, EPSS; pre-ejection period, PEP; ejection time, LVET; ratio of PEP to LVET; velocity of circumferential shortening, Vcf, LV end-diastolic volume index (LVEDVI) and LV end-systolic volume index (LVESVI) on admission and 6, 24, 48 and 72 h later in septic calves and once in healthy calves. Admission data were compared using the Mann-Whitney U test and P < .05 was considered significant. Decreased preload and afterload were present in septic calves, as indicated by marked decreases in BP, LVEDVI, LVESVI, SVI, CI, EPSS when compared to healthy calves. Systolic function appeared adequate in septic calves, based on EF and FS compared to control calves. There was no difference in heart rate, LVET, PEP:LVET, or Vcf between septic and health calves. We conclude that circulatory dysfunction, rather than systolic dysfunction predominates in septic calves. Positive associations on admission between CI and LVEDVI, LVESVI, and SVI support this conclusion. Echocardiographic determination of LVEDVI and CI appears useful in directing treatment in septic calves. Highlights: LVEDV and LVESV from echocardiographic measurements of LV dimensions indicated that an absolute or relative decrease in central blood volume was an important cardiovascular derangement in septic calves. EF was not a useful index of systolic performance in this case series, as there was no difference in EF between healthy and septic calves. Circulatory dysfunction (decreased preload and afterload), rather than systolic dysfunction, was the most clinically important cardiovascular abnormality in septic calves.